Nonstandard transfinite electrical networks - A. H. Zemanian (Հայաստանի ԳԱԱ)
The idea of a nonstandard, transfinite, linear electrical network is defined. To prove an existence and uniqueness theorem for a hyperreal current-voltage regime, the concept of a transfinite graph has to lifted info a nonstandard setting. Nonstandard versions of Kirchhoff's laws are also examined. Finally, it is poited out that certain nonlinear networks have unique hyperreal current-voltage regimes as well. Реализована идея нестандартной, трансконечной, линейной электрической сети. Чтобы доказать теорему существования и единственности для гипервещественного режима напряжения тока, понятие трансконечного графа должно быть распространено на нестандартные положения. Проверяются также нестандартные версии законов Хирчова. Наконец, указывается, что некоторые нелинейные сети также имеют единственные гипервещественные режимы напряжения тока.
Keywords: Mathematics; Science